2023
DOI: 10.1002/ehf2.14225
|View full text |Cite
|
Sign up to set email alerts
|

Mean corpuscular haemoglobin concentration and outcomes in heart failure with preserved ejection fraction

Abstract: Aims This study aims to evaluate the prognostic value of mean corpuscular haemoglobin concentration (MCHC) on clinical outcomes in patients with heart failure with preserved ejection fraction (HFpEF). Methods and results We analysed HFpEF participants from the Americas in the Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist (TOPCAT) trial with available baseline data ( n = 1747). Patients were grouped into h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Morteza et, al . 35 compared various RBC indices to predict a 12-month prognosis in heart failure. Among the above, the MCHC was the most sensitive index, and RDW was the most specific 35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morteza et, al . 35 compared various RBC indices to predict a 12-month prognosis in heart failure. Among the above, the MCHC was the most sensitive index, and RDW was the most specific 35 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, RDW 33 and MCHC 34 have already been recognized as diagnostic indicators of anaemia, and HSW is calculated from MCHC and RDW. MCHC mirrors the haemoglobin concentration and is related to an adverse poor prognosis in heart failure 35 (a subtype of CVD). Higher RDW 36 mirrors the potential deregulation of RBC balance, including weakened erythropoiesis and disorder RBC survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model 1 showed that greater fluid management increases the risk of AHF. Relative erythrocyte hypochromia, which manifests as a low MCHC, affects the onset of AHF [40, 41]; a decrease in the MCHC corresponds to an increase in the risk of AHF. The serum bicarbonate level also significantly increases in patients with AHF [42], and it can serve as a predictive indicator.…”
Section: Discussionmentioning
confidence: 99%
“…as diagnostic indicators of anaemia, and HSW is calculated from MCHC and RDW. MCHC mirrors the haemoglobin concentration and is related to an adverse poor prognosis in heart failure 29 . Higher RDW 2 mirrors the potential deregulation of RBC balance, including weakened erythropoiesis and disorder RBC survival.…”
Section: Discussionmentioning
confidence: 99%